Combining ability of highland tropic adapted potato for tuber yield and yield components under drought - Hirut, B.; Shimelis, Hussein; Fentahun, M.; Bonierbale, Merideth W.; Gastelo, M.; Asfaw, A. (Public Library of Science, 2017)
Recurrent drought and late blight disease are the major factors limiting potato productivity in the northwest Ethiopian highlands. Incorporating drought tolerance and late blight resistance in the same genotypes will enable the development of cultivars with high and stable yield potential under erratic rainfall conditions. The objectives of this study were to assess combining ability effects and gene action for tuber yield and traits related to drought tolerance in the International Potato Centre’s (CIP’s) advanced clones from the late blight resistant breeding population B group ‘B3C2’ and to identify promising parents and families for cultivar development. Sixteen advanced clones from the late blight resistant breeding population were crossed in two sets using the North Carolina Design II. The resulting 32 families were evaluated together with five checks and 12 parental clones in a 7 x 7 lattice design with two water regimes and two replications. The experiment was carried out at Adet, in northwest Ethiopia under well-watered and water stressed conditions with terminal drought imposed from the tuber bulking stage. The results showed highly significant differences between families, checks, and parents for growth, physiological, and tuber yield related traits. Traits including marketable tuber yield, marketable tuber number, average tuber weight and groundcover were positively correlated with total tuber yield under both drought stressed and well-watered conditions. Plant height was correlated with yield only under drought stressed condition. GCA was more important than SCA for total tuber yield, marketable tuber yield, average tuber weight, plant height, groundcover, and chlorophyll content under stress. This study identified the parents with best GCA and the combinations with best SCA effects, for both tuber yield and drought tolerance related traits. The new population is shown to be a valuable genetic resource for variety selection and improvement of potato’s adaptation to the drought prone areas in northwest Ethiopia and similar environments.